Sustained delivery of vascular endothelial growth factor from mesoporous calcium‐deficient hydroxyapatite microparticles promotes in vitro angiogenesis and osteogenesis. Issue 7 (21st September 2020) - Piard, Charlotte; Luthcke, Rachel; Kamalitdinov, Timur; Fisher, John
Abstract: Promoting the growth of blood vessels within engineered tissues remains one of the main challenge in bone tissue engineering. One way to improve angiogenesis is the use of vascular endothelial growth factor (VEGF) as it holds the ability to increase the formation of a vascular network. In the present study, collagen scaffolds with VEGF‐releasing hydroxyapatite particles were fabricated, in order to engineer a material both capable of presenting an osteoconductive surface and delivering an angiogenic growth factor in a localized and sustained manner, in order to enhance osteogenesis as well as angiogenesis. To this end, we developed microparticles and characterize their size, chemical properties and Ca/P ratio to validate the formation of hydroxyapatite. We then evaluated the osteogenic potential of HAp when cultured with mesenchymal stem cells and compare it to commercially available hydroxyapatite (SBp). Finally, we characterized the encapsulation and release of VEGF in the HAp and assess the angiogenic potential of the VEGF‐HAp when cultured with endothelial cells. We demonstrated the successful fabrication of calcium deficient hydroxyapatite microparticles (CDHAp), with biological properties closer to the bone than stoichiometric, commercially available hydroxyapatite. This CDHAp exhibited a well‐defined 3D network of crystalline nanoplates forming mesoporous and hollow structures. The high specific area created by those structures enabled the loading of VEGF with high efficiency when compared to the loading efficiency of SBp. Furthermore, their biological performances were evaluated in vitro. Our results indicate that VEGF‐CDHAp can be used to improve both osteogenesis and angiogenesis in vitro.